Anti-metastatic and anti-angiogenic effects of curcumin analog DK1 on human osteosarcoma cells in vitro - Muhammad Nazirul Mubin Aziz; Nurul Fattin Che Rahim; Yazmin Hussin; Yeap, Swee Keong; Mas Jaffri Masarudin; Nurul Elyani Mohamad; Muhammad Nadeem Akhtar; Mohd Azuraidi Osman; Cheah, Yoke Kqueen; Noorjahan Banu Alitheen (Multidisciplinary Digital Publishing Institute, 2021)
Osteosarcoma (OS) is a life-threatening malignant bone tumor associated with poor prognosis among children. The survival rate of the patient is still arguably low even with intensive treatment provided, plus with the inherent side effects from the chemotherapy, which gives more unfavorable outcomes. Hence, the search for potent anti-osteosarcoma agent with promising safety profile is still on going. Natural occurring substance like curcumin has gained a lot of attention due to its splendid safety profile as well as it pharmacological advantages such as anti-metastasis and anti-angiogenesis. However, natural curcumin was widely known for its poor cellular uptake, which undermines all potential that it possesses. This prompted the development of synthetically synthesized curcuminoid analog, known as (Z)-3-hydroxy-1-(2-hydroxyphenyl)-3-phenylprop-2- en-1-one (DK1). In this present study, in vitro scratch assay, transwell migration/invasion assay, HUVEC tube formation assay, and ex vivo rat aortic ring assays were performed in order to investigate the anti-metastatic and anti-angiogenic potential of DK1. For further comprehension of DK1 mechanism on human osteosarcoma cell lines, microarray gene expression analysis, quantitative polymerase chain reaction (qPCR), and proteome profiler were adopted, providing valuable forecast from the expression of important genes and proteins related to metastasis and angiogenesis. Based on the data gathered from the bioassays, DK1 was able to inhibit the metastasis and angiogenesis of human osteosarcoma cell lines by significantly reducing the cell motility, number of migrated and invaded cells as well as the tube formation and micro-vessels sprouting. Additionally, DK1 also has significantly regulated several cancer pathways involved in OS proliferation, metastasis, and angiogenesis such as PI3K/Akt and NF-κB in both U-2 OS and MG-63. Regulation of PI3K/Akt caused up-regulation of genes related to metastasis inhibition, namely, PTEN, FOXO, PLK3, and GADD45A. Meanwhile, NF-κB pathway was regulated by mitigating the expression of NF-κB activator such as IKBKB and IKBKE in MG-63, whilst up-regulating the expression of NF-κB inhibitors such as NFKBIA and NFKBIE in U-2 OS. Finally, DK1 also has successfully hindered the metastatic and angiogenic capability of OS cell lines by down-regulating the expression of pro-metastatic genes and proteins like MMP3, COL11A1, FGF1, Endoglin, uPA, and IGFBP2 in U-2 OS. Whilst for MG-63, the significantly down-regulated oncogenes were Serpin E1, AKT2, VEGF, uPA, PD-ECGF, and Endoglin. These results suggest that curcumin analog DK1 may serve as a potential new anti-osteosarcoma agent due to its anti-metastatic and anti-angiogenic attributes.